OLD BOOKS AND NEW HISTORIES: AN ORIENTATION TO STUDIES IN BOOK AND PRINT CULTURE - HOWSAM, LESLIE (Knygotyra, 2013)
Studies in the culture and history of the book are a burgeoning academic specialty. Intriguing, rigorous, and vital, they are nevertheless rooted within three major academic disciplines – history, literary studies, and bibliography – that focus respectively upon the book as a cultural transaction, a literary text, and a material artefact. Old books and New Histories serves as a guide to this rich but sometimes confusing territory, explaining how different scholary approaches to what may appear to be the same entity can lead to divergent questions and contradictory answers.